2019
DOI: 10.1038/s41598-019-40760-x
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethylene bisacetamide impairs NK cell-mediated clearance of acute T lymphoblastic leukemia cells and HIV-1-infected T cells that exit viral latency

Abstract: The hexamethylene bisacetamide (HMBA) anticancer drug was dismissed due to limited efficacy in leukemic patients but it may re-enter into the clinics in HIV-1 eradication strategies because of its recently disclosed capacity to reactivate latent virus. Here, we investigated the impact of HMBA on the cytotoxicity of natural killer (NK) cells against acute T lymphoblastic leukemia (T-ALL) cells or HIV-1-infected T cells that exit from latency. We show that in T-ALL cells HMBA upmodulated MICB and ULBP2 ligands f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Latency reversing agents (LRAs), known as drugs able to induce viral production and unmask latently-infected cells, represent a promising clinical approach to cure HIV-1 [198,199]. LRAs promote “shock-and-kill” immune-mediated mechanisms, including those dependent on NK cells [200,201,202]. Interestingly, in the context of HIV-1, some LRAs have the potential to induce DNAM-1 ligands on CD4 + T cells [200]; therefore, it will be important to evaluate the contribution of DNAM-1-mediated responses of NK cells against HIV-1 infection upon the “shock-and-kill” triggering.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Latency reversing agents (LRAs), known as drugs able to induce viral production and unmask latently-infected cells, represent a promising clinical approach to cure HIV-1 [198,199]. LRAs promote “shock-and-kill” immune-mediated mechanisms, including those dependent on NK cells [200,201,202]. Interestingly, in the context of HIV-1, some LRAs have the potential to induce DNAM-1 ligands on CD4 + T cells [200]; therefore, it will be important to evaluate the contribution of DNAM-1-mediated responses of NK cells against HIV-1 infection upon the “shock-and-kill” triggering.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Many tumors have been known to overexpress stress-induced ligands that can stimulate NK cell activity (2,3). Like many of these tumors, Jurkat cells have been shown to express NK cell ligands (22,23). These ligands could potentially synergize with costimulatory receptor signaling to promote NK cell-mediated cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…When expression of NK cell activating receptors was analyzed, various HDACis showed diverse negative effects, the worse being observed with Panobinostat that downregulated all activating receptors including NKG2D [84]. Recently, we showed that ex vivo NK cell exposure to a BETi compound, HMBA, reduced expression of NKG2D and its DAP10 adaptor molecule, impairing NKG2D-mediated cytotoxicity and dampening NK cell capacity to respond to IL-15 stimulation which is dependent on DAP10 [87]. Conversely, work performed by different groups including ours have shown that exposure to Prostratin results in overall activation of NK cells associated with upmodulation of NKG2D and NKp44 receptors, shedding of CD16, and, most importantly, in an enhanced NK cell-mediated clearance of T cells latently or productively infected with HIV-1 [25,84,85].…”
Section: Impact Of Lras On Nk Cell Phenotype and Functionmentioning
confidence: 99%